2014
DOI: 10.17648/heringeriana.v6i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Macrófitas aquáticas do Pantanal e de outras áreas úmidas em Mato Grosso do Sul

Abstract: Esta é uma breve revisão de alguns trabalhos recentes sobre diversidade de plantas aquáticas do Pantanal, da planície de inundação do Rio Paraná e de outras áreas úmidas de Mato Grosso do Sul, com algumas considerações florísticas. As áreas extra-planícies dos dois grandes rios são nascentes, veredas, campos úmidos, covais e varjões dos cerrados e da floresta estacionai, além de águas cristalinas de Bonito. A planície do Rio Paraná tem a menor área e 153 espécies, o Pantanal, com a maior área, tem 280 espécies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
8
0
6
Order By: Relevance
“…Thus, more conspicuous, larger-flowered species during the rains may suffer higher rates of florivore attack. Seasonality may also limit the substrate where plants occur (e.g., aquatic and terrestrial substrate from wetlands; Pott and Pott 2000), which, ultimately, may also influence flowering (Fava and Gomes, 2017;Souza et al, 2018Souza et al, , 2020. It is reasonable, therefore, to expect a potential simultaneous influence of environmental conditions such as the hydrological processes and plant substrate, together with the seasonal variation in flower size on the attraction and occurrence of florivores.…”
mentioning
confidence: 99%
“…Thus, more conspicuous, larger-flowered species during the rains may suffer higher rates of florivore attack. Seasonality may also limit the substrate where plants occur (e.g., aquatic and terrestrial substrate from wetlands; Pott and Pott 2000), which, ultimately, may also influence flowering (Fava and Gomes, 2017;Souza et al, 2018Souza et al, , 2020. It is reasonable, therefore, to expect a potential simultaneous influence of environmental conditions such as the hydrological processes and plant substrate, together with the seasonal variation in flower size on the attraction and occurrence of florivores.…”
mentioning
confidence: 99%
“…For the latter studies, there might not be Regarding the species of Senna reported by us, Moura et al (2018) highlight that due to the genus' poricidal anthers, pollen is their only floral resource. The sharing of bee species between certain areas seems to indicate the existence of a foraging pattern between bee species, which includes Apis mellifera, that despite foraging a wide range of plants species, shows a clear preference for certain species in each area (Aguiar et al 2002;Pott & Pott 1986). This can be attributed to the occurrence of distinct and predominant vegetation types in each area.…”
Section: Diversity Of the Bee Floramentioning
confidence: 99%
“…No Pantanal, são responsáveis pela ciclagem de nutrientes do solo durante os períodos de seca, quando a superfície inundada diminui e a matéria orgânica dessas plantas se decompõe (POTT e POTT, 2000). Também são muito importantes na cadeia trófica dos ecossistemas aquáticos pois servem como abrigo e alimento para peixes, insetos aquáticos, moluscos, aves e mamíferos, além de servirem como substrato ao perifíton (POTT & POTT, 2009). Outra característica que agrega valor à essas espécies é sua capacidade "filtradora", fazendo a retenção de nutrientes, sedimentos e até mesmo de alguns grupos de poluentes em suspensão (HAMILTON 1993;SIPAÚBA-TAVARES et al 2003).…”
Section: Caracterização Das Plantas Aquáticasunclassified